Influence of Geodetic Works on the Road Pavement Evenness in the Highways Construction - Ilchenko, Volodymyr; Tkachenko, Iryna; Kozar, Valentyn; Kozar, Larysa (International Journal of Engineering and Technology, 2018)
The regulatory requirements and methods of road pavement evenness monitoring in the highway construction have been considered. The constituents and the marginal error magnitude, which should be taken into account for the highway pavement evenness estimation, have been substantiated. The fixing design schemes and the stringline deviation from the planned position during geodetic placement works on horizontal and inclined sections and vertical curves sections have been defined. The necessary marking points interval of fixing stringline, which ensures the reproduction accuracy in the vertical alignment terrain and necessary surface evenness of highway pavement, has been defined.